Exploring Well-being at Work—An Interview Study on How IT Professionals Perceive Their Workplace - Zutavern, Stefanie; Seifried, Jürgen (Frontiers in Psychology, 2021)
The workplace is particularly important for promoting well-being at work and general life satisfaction, as performing a professional activity can be perceived as satisfying and motivating. In addition, employment opens up opportunities for individual development that employees may be perceived as fulfilling. By conducting an interview study with IT professionals of a German medium-sized company, we investigate which factors of the individual work environment are perceived as conducive to the performance of everyday job duties and thus increase well-being at work. Furthermore, we analyze the extent to which participants are satisfied with the implementation of the factors that are important to them, whether socio-demographic differences are relevant, and whether the perception of the work environment has an effect on employees’ commitment. Results show that interpersonal factors in particular are considered to be important in everyday working life. About individual factors, a mixed picture emerged, whereby sociodemographic differences play only a minor role. Furthermore, there are indications of a positive relationship between the perception of the work environment and the IT professionals’ commitment. In-depth analysis of the employee statements helps to determine which aspects of the work environment should be implemented, developed or promoted. In the long term, this can support individual learning and development paths and generates a work environment that sustainably promotes employees’ well-being at work and fosters long-term employment relationships.